3D Vertically Aligned Microchannel Three‐Layer All Ceramic Lithium Ion Battery for High‐Rate and Long‐Cycle Electrochemical Energy Storage. Issue 13 (6th February 2022) - Ji, Shuaijing; Wang, Xinjian; Li, Kunze; Huan, Yu; Ma, Guanjun; Su, Yuanhui; Wei, Tao
Abstract: Due to the growing energy and safety demands, rechargeable all‐solid‐state Li + batteries using metallic Li anode and ceramic‐based electrolytes have attracted extensive attentions. However, the inherent safety problem of Li metal anode, the ceramic‐electrode low Li + conductivity, and the high electrolyte/electrode solid–solid interfacial impedance slow the development of high‐performance all‐solid‐state batteries. In this work, a three‐layer all ceramic battery with Li4 Ti5 O12 ceramic as anode, LiCoO2 as cathode, and Li0.34 La0.56 TiO3 as electrolyte to solve the safety problem is proposed. The low Li + conductivity of electrodes are effectively addressed by fabricating the electrode/electrolyte composite electrodes in 3D vertically aligned microchannel structures. The large interfacial impedance is greatly reduced by co‐constructing the microchannel‐dense‐microchannel structure with high Li + conducting electrolytes. Experimental results reveal that a working cell by applying the 3D vertically aligned microchannel three‐layer all ceramic structure enables high energy storage at 2 C rate and long cycling stability for more than 500 times. Abstract : A 3D vertically aligned microchannel three‐layer all ceramic lithium ion battery with Li4 Ti5 O12 as anode, LiCoO2 as cathode, and Li0.34 La0.56 TiO3 as electrolyte is constructed. The all‐ceramic structure solves the safety problem. The electrode/electrolyte composites in 3D vertically aligned microchannel structures enhance the Li + conductivity of electrode layers.